Human Occupation in the Eastern Foothill of San Luis Hills: Analysis of Site Las Barranquitas (Department of Coronel Pringles, San Luis Province) - Carrera Aizpitarte, Manuel; Cena Di Matteo, Malena (Facultad de Filosofía y Letras, Universidad Nacional de Cuyo, 2024)
Las Barranquitas is a site located in the foothill of the San Luis Hill. Its archaeological record is composed mainly of lithic artifacts, and to a lesser extent ceramic and bone fragments. The materials were obtained under different collection circumstances, so they were divided into two sets for analysis. Set A is made up of the items obtained on a dirt road and in the adjacent ravine, while those of set B come from systematic surveys carried out in the field that is located adjacent to the road. In both sets the most used raw material are quartz and siliceous rocks. The aim of this paper is to compare the information generated in each set and link it with the occupation process of this space. In addition, it seeks to investigate the origin of lithic resources and their relationship with rock management and the mobility circuits of human groups. The macroscopic characteristics of the raw materials indicate that they were mainly obtained from nearby sources that did not involve large procurement costs. On the other hand, the differential presence of typological groups suggests that set A could present materials from different stratigraphic levels and corresponding to different chronologies, while set B could be limited to later moments. In this way, it is proposed that Las Barranquitas could have been a space occupied repeatedly, from the early/middle Holocene to the final late Holocene.